Criminal Liability for Forest Burning in Indonesia - Hasudungan Sinaga (Journal of Social Science, 2023)
Degradation of the forest environment has a huge negative effect on the environment, economy, institutions, as well as society, especially in terms of accessibility of forest resources and biodiversity. Forest and land fires (“Karhutla”) in Indonesia have increased drastically this year during the dry season, according to the non-profit organization Madani Sustainable. Based on their monitoring findings, an area of 152,678 hectares is an indicative area for land fires and forest and land fires in Indonesia in August 2023 alone. This study aims to determine criminal liability for forest burning in Indonesia. This research uses normative legal methods which are supported by literature reviews from various scientific journal sources published in 2019-2023. The research results show that criminal liability has been regulated in Article 108 of Law Number 32 of 2009 concerning Environmental Management.